Hubungan Antara Emosi Malu Tehadap Gaya Pertautan dan Motivasi Pencapaian Dalam kalangan Pelajar: Satu Kajian Meta Analisis (Sains Humanika, 2018)
Shame emotion is a factor that contributes to student’s attachment style and the declination and increment of their achievement motivation to succeed. Shame is an emotion that is significant among students especially during their school years which is the period before they enrolling in a university. This will effect their attachement style either towards their parents, teachers or peers and and will have an impact on the level of motivation of students achieving what they want in the academic field.Therefore, this study aims to identify the elements in the relationship between shame emotions on the style of achievement and achievement motivation among students based on past studies through meta analysis techniques.After qualitative analysis, there are two recognizable relationships which are the relationship between shame emotion with attachment styles and shame emotions with achievement motivation.
Keywords: shame emotion; attachment style; motivation achievement; shame; motivation